Monitoring core temperature of firefighters to validate a wearable non-invasive core thermometer in different types of protective clothing: Concurrent in-vivo validation. (February 2020) - Roossien, C.C.; Heus, R.; Reneman, M.F.; Verkerke, G.J.
Abstract: This study aims (1) to test the validity of a new non-invasive core thermometer, Cosinuss°, in rest and (2) during firefighting simulation tasks, against invasive temperature pill and inner-ear temperature and (3) to compare the change in core temperature of firefighters when working in two types of protective clothing (traditional turnout gear versus new concept). 11 active firefighters performed twice a selection of tasks during their periodic preventive medical examination and a fire-extinguishing task. Without correction no correlation between the Cosinuss° and thermometer pill (ICC≤0.09, p ≥ 0.154, LoA≥1.37) and a moderate correlation between Cosinuss° and inner-ear infrared (ICC = 0.40, p = 0.044, LoA±1.20) was observed. With individual correction both correlations were excellent (ICC≥0.84, p = 0.000, LoA≤0.30). However, during and after working all correlations were poor and non-significant (ICC≤0.38, p ≥ 0.091, LoA≥1.71). During firefighting tasks, the Cosinuss° is invalid for measuring the core temperature. No differences in heat development in the two types of protective clothing was proven. Highlights: A wearable, non-invasive core thermometer could prevent heat related illnesses. Calibration of the Cosinuss° is required and resulted in a valid and reliable system. During and after firefighting tasks, all correlations were non-significantly poor. Cosinuss° C-med is an invalid method for measuring core temperature during work. The heat development in the two types of protective clothing did not differ majorly.